2019
DOI: 10.1101/758813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning improves decoding of odor identity with phase-referenced oscillations in the olfactory bulb

Abstract: Local field potential oscillations reflect temporally coordinated neuronal ensembles— coupling distant brain regions, gating processing windows, and providing a reference for spike timing-based codes. In phase amplitude coupling (PAC), the amplitude of the envelope of a faster oscillation is larger within a phase window of a slower carrier wave. Here, we characterized PAC, and the related theta phase-referenced high gamma and beta power (PRP), in the olfactory bulb of mice learning to discriminate odorants. PA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 97 publications
2
26
0
Order By: Relevance
“…This process is accompanied by gamma oscillations [ 121 ], including low (40–70 Hz) and high (70–100 Hz) gamma [ 88 ]. Besides gamma oscillations, phase-amplitude coupling was also reported to be involved in the processing of odor information [ 95 ]. Deficits in both OB gamma network oscillations and phase-amplitude coupling were found in aging and AD mice [ 2 4 , 12 ].…”
Section: Ad-related Olfactory Deficits Are Recapitulated In Mouse Modmentioning
confidence: 99%
“…This process is accompanied by gamma oscillations [ 121 ], including low (40–70 Hz) and high (70–100 Hz) gamma [ 88 ]. Besides gamma oscillations, phase-amplitude coupling was also reported to be involved in the processing of odor information [ 95 ]. Deficits in both OB gamma network oscillations and phase-amplitude coupling were found in aging and AD mice [ 2 4 , 12 ].…”
Section: Ad-related Olfactory Deficits Are Recapitulated In Mouse Modmentioning
confidence: 99%
“…33 Oscillations recorded from the OB contain crucial information on chemical properties of the odour and as well as odour identity encoding during olfactory learning. 34,35 Thus, we next compared the LFP signals in awake mice before and after direct application of oxytocin into the OB. The raw LFP signals were divided into theta (2-12 Hz), beta , low gamma (36-65 Hz) and high gamma (66-95 Hz) bands (Figure 4A).…”
Section: Oxytocin Decreases the Amplitude Of Odour-evoked High Gammmentioning
confidence: 99%
“…Different functional roles have been attributed to PAC, including sensory signal detection (Händel and Haarmeier 2009), executive functions (Tort et al 2009), and attentional selection (Schroeder and Lakatos 2009). Specifically for olfaction, it has recently been demonstrated that PAC in the OB shapes early sensory processing in mice (Losacco et al 2020). Given this, we examined PAC between beta and gamma oscillation within the OB and its relation to the processing of the individual's odor valence using RSA.…”
Section: Early Phase Amplitude Coupling Between Beta and Gamma In Obmentioning
confidence: 99%